2013
DOI: 10.1177/0300060513483416
|View full text |Cite
|
Sign up to set email alerts
|

Correlative analysis of social support with anxiety and depression in men undergoing in vitro fertilization embryo transfer for the first time

Abstract: Objective: To explore the correlation between the level of social support and the extent of anxiety and depression in Chinese men undergoing in vitro fertilization embryo transfer (IVF-ET) for the first time, in order to provide a basis for male mental health counselling. Methods: Self-administered questionnaires covering general health status, anxiety (self-rating anxiety scale), depression (self-rating depression scale) and social support (social support rating scale) were completed by men undergoing their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
2
11
0
2
Order By: Relevance
“…The depression levels of women and/or men were investigated in the nine studies using a variety of instruments: the Beck Depression Inventory (BDI) [11,20,24], the Symptom Check List (SCL-90) [5,23], the Self-Rating Depression Scale (SDS) [19], the Psychological General Well-Being Index (PGWB) [6], the Patient Health Questionnaire-9 (PHQ-9) [21], and the Lubin's Depression Adjective Checklist Scale (DACL) [22]. The depression levels of women before proceeding with IVF treatment were presented in seven studies.…”
Section: Depressionmentioning
confidence: 99%
See 3 more Smart Citations
“…The depression levels of women and/or men were investigated in the nine studies using a variety of instruments: the Beck Depression Inventory (BDI) [11,20,24], the Symptom Check List (SCL-90) [5,23], the Self-Rating Depression Scale (SDS) [19], the Psychological General Well-Being Index (PGWB) [6], the Patient Health Questionnaire-9 (PHQ-9) [21], and the Lubin's Depression Adjective Checklist Scale (DACL) [22]. The depression levels of women before proceeding with IVF treatment were presented in seven studies.…”
Section: Depressionmentioning
confidence: 99%
“…Two of the four studies that examined the depression status of infertile men also showed that these men exhibited more symptoms of depression than fertile men [19], or a higher incidence of moderate and severe depression (BDI ≥ 10, IVF vs. ICSI vs. control = 44 % vs. 26.7 % vs. 24 %) [11].…”
Section: Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Лечебно-диагностические проце-дуры, многочисленные попытки забеременеть, ожидания, разочарования нередко приводят (или наслаиваются) к психоэмоциональным расстройствам. Нервно-психический фактор как причина, усугубляющая бесплодие, явля-ется общепризнанным среди специалистов раз-личных клинических дисциплин [4][5][6].…”
unclassified